PENGEMBANGAN EKONOMI KREATIF KWT SEJAHTERA KECAMATAN KAWAY XVI MELALUI PENERAPAN ECO-MARKET ‘GERAISTOK’ DAN STRATEGI MARKETING MIX - Fuqara, Fantashir Awwal; Lisa, Oviana; Mulyana, Agusriati; Tanjung, Yulia Windi; Aminah, Siti; Hasibuan, Rony Rahmat Hidayat; Herliana, Herliana; Firwanda, Muhammad Rizki (Jurnal Abdi Insani, 2025)
This community service program aims to enhance the capacity of the Kelompok Wanita Tani (KWT) Sejahtera in Kaway XIV Subdistrict, West Aceh Regency, to manage agricultural-based enterprises through the adoption of the Geraistok eco-market technology integrated with a marketing mix strategy. The program was initiated in response to the group’s limited market access, lack of modern technology adoption, and insufficient marketing strategies, which have hindered the optimal development of its creative economy potential. The activities were conducted from August to September, targeting 15 active members of KWT Sejahtera engaged in the production and marketing of agricultural products, particularly minaponic-based horticulture. The implementation method included participatory planning, preparation of sustainable materials and tools, construction of an eco-market stock outlet, training on business management, packaging innovation, flexible pricing strategies, distribution planning, and integrated online and offline promotion. The results indicated significant improvements in marketing infrastructure through a strategically located physical outlet and a digital platform that expanded market reach beyond the local area. Environmentally friendly packaging innovations and product identity labeling strengthened brand image and increased consumer appeal, particularly among the middle to upper market segments. The application of the marketing mix proved effective in boosting sales, enhancing members’ competencies, and expanding business partnerships. In the long term, this program establishes a replicable model for rural women’s empowerment that is adaptive, competitive, and sustainable. By integrating eco-market technology with modern marketing strategies, KWT Sejahtera has the potential to become a pioneer in developing an inclusive, competitive, and environmentally friendly agricultural creative economy ecosystem.